Design of optimal rainfall networks by means of principal components analysis - Herman de Bautista, Susana; Donoso, Arnaldo (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper presents a procedure for the design of optimal raingage networks to obtain the mean areal precipitation of monthly rain over a fixed area. It is based on the multivariate technique of Principal Components considering both density and location of the observations. In proportion to the increase of stations, the variance of the mean area precipitation estimated from the network observations toward the real variance. The variance is calculated as the first eigenvalue of the correlation matrix. The accuracy of the network is defined in terms of its capability to represent the real spatial variability of the events.